Summary Record of Annual Conference on Community Development Held at Mount Abu - Ministry of Community Development Government of India (Ministry of Community Development Government of India, 1958)
The Annual Conference on Community Development held at Mount Abu in May 1958, along with subsequent thematic deliberations, represents a foundational phase in India’s post-independence rural development strategy. The discussions emphasized a holistic and participatory model of development that integrates agriculture, education, health, housing, infrastructure, and local governance within a framework of democratic decentralization. Central to the approach was the belief that sustainable rural progress depends on active community participation, effective local leadership, and strong institutional support at the block and village levels. The conference and related documents highlighted the need to strengthen agricultural productivity through improved seeds, minor irrigation, animal husbandry, fisheries, and poultry development, while simultaneously promoting cooperative institutions to ensure equitable distribution of economic benefits. Special attention was given to training and capacity building of village-level workers, educators, artisans, and administrative personnel to enhance efficiency and responsiveness in implementation. The role of Panchayati Raj institutions, Gramdan villages, and cooperative societies was underscored as vital for empowering communities and fostering self-reliance. Furthermore, the deliberations addressed critical social sectors including women and child welfare, tribal development, rural housing, health and sanitation, education, and cultural promotion. Administrative reforms, improved coordination among departments, systematic data collection, and continuous evaluation were identified as essential for overcoming implementation challenges. Overall, the conference proceedings and associated recommendations laid the groundwork for an integrated, people-centered development paradigm aimed at transforming rural India through collective responsibility, institutional strengthening, and sustained community engagement.
Ministry of Community Development Government of India
Keywords: Community Development Programme; Democratic Decentralization; Rural Development; Agricultural Production; Cooperative Institutions; Gramdan Movement; Panchayati Raj; Capacity Building; Women and Child Welfare; Minor Irrigation; Industrial Cooperatives; Administrative Reforms